International and American Students' Perceptions of Informal English Conversations - Lee, Eun Jeong (Esther) (Journal of International Students, 2016)
This study investigated international and American students’ perceptions of structured but informal English conversations with each other. American and international students perceived the effects of these conversations differently. While the international students claimed increased linguistic and cultural competence, the Americans identified cultural exchange as the main benefit: they shared their own cultures and experiences and learned more about their conversation partners’ home countries. Both sets of participants associated these benefits with a non-threatening and non-judgmental atmosphere and emphasized the importance of comfort and friendship. Understanding these expectations and assessments can help ESL program administrators design effective informal conversation programs, and help identify opportunities for ESL improvement outside of formal coursework.